Продуктивні якості лактуючих корів промислового комплексу за тривалого періоду яловості та безпліддя - Гуцуляк, Ганна Сергіївна; Hutsuliak, Н. S.; Gutsulyak, G. S.; Hutsuliak, Hanna Serhiivna; Hutsuliak, Hanna; Huculak, A. (Дніпровський ДАЕУ, 2021)
В дисертаційній роботі викладені матеріали досліджень продуктивних та відтворних якостей голштинських корів за інтенсивної технології їх експлуатації. Ретроспективний аналіз стада та експерименти показали, що жива маса лактуючих голштинських корів упродовж господарського використання має динамічний характер, за якого вона нарощується до третьої лактації, потім йде невпинний її спад до п’ятої лактації. Натомість, реалізація генетичного потенціалу молочної продуктивності збільшується до четвертої лактації, а лише потім знижується. Стадо корів промислового комплексу характеризується задовільними показниками відтворної функції, за яких може проявлятися скорочена, стандартна, подовжена та тривала лактація. Встановлено, що морфологічний склад крові різновікових корів за різної тривалості лактаційного періоду знаходиться в основному в межах референтних значень. Біохімічні показники сироватки крові корів мають більш істотні вікові відмінності, ніж зміни, пов’язані з тривалістю лактаційного періоду. Доведено, що за подовженого та тривалого лактаційного періоду у корів різного віку суттєво порушується баланс між станом організму та зовнішнім середовищем. Подовжена та тривала лактація у корів є наслідком низької відтворної функції, через що збільшується тривалість безпліддя та відповідне недоотримання приплоду і втрати молока. Встановлено, що чим вища молочна продуктивність корів, тим вища її вартість і додаткові витрати кормів, на її отримання, не перевищують вартість додаткової продукції, що і забезпечує економічну ефективність виробництва. In dissertation work presents the materials of research of the productive and reproductive qualities of Holstein cows in the conditions of industrial technology of milk production. A retrospective analysis of the herd and the experiments showed that the live weight of Holstein cows during exploitation has a dynamic character, increases from 594.4 kg in first-heifers to 673.0 kg in cows of the third lactation, and then decreases to 584.0 kg. At the same time, the realization of the genetic potential of the milk productivity of cows increases until the fourth lactation and is, in terms of 305 days, an average of 9575.2 kg (9391.5 kg of 4% milk), after which it decreases to a level of 9325.8 kg (9171.8 kg of 4% milk). Such dynamics of the main characteristics indicates some physical and physiological depletion of animals by intensive exploitation technology. In general, the herd of animals is characterized by high milk productivity and acceptable indicators of reproductive function. As a result, in lactating cows appear the abbreviated (246.6–251.8 days), standard, extended (561.2–610.9 days) and prolonged (845.9–915.5 days) lactation function. During abbreviated lactation, cows' milk yield does not fall below 5774.0 kg, although it does not exceed 6645.8 kg of milk. During standard lactation, first-heifers are characterized by the relatively lowest milk yield – 8052.3 kg of milk and the most highly productive is third lactation cows – 9616.8 kg. It was found that with a lactation period of 561.2–610.9 days, milk yield of cows of different ages dynamically grows from the first lactation at the level of 7944.1 kg in terms of 305 days to 9716.7 kg in animals of the fifth and older lactations. At the same time, the live weight of animals primarily increases from the first to the third lactation, where it acquires its maximum value – 691.6 kg, and then gradually decreases to the indicator of first-heifers – 577.0 kg, where the highest coefficient of milk production – 2742.3 kg. Animals are characterized by low indicators of reproductive ability, since the period between calving lasts 612.8–661.8 days. It has been proved that with a lactation function of 845.9–915.5 days, milk productivity increases with age up to 11399.2 kg in fourth-lactation cows. At the same time, first-heifers have the highest coefficient of milk productivity is 3329.8 kg. The service period in animals lasts on average 611.9–681.5 days, and the period between calving lasts 897.5–967.1 days. It was found that the morphological composition of the blood of experimental Holstein cows of different ages in indicators of the concentration of erythrocytes (5.6–5.8 g/l), leukocytes (8.1–9.0 g/l) and platelets (346.8–373.7 g/l) is mainly within the reference values. At the same time, in cows with a extended lactation period, the total protein content is higher by 8.0 %, albumin – by 6.7%, hemoglobin – by 1.5 %, and ALT activity is also higher – by 9.2 %, compared to with animals with a standard lactation period. Some increased biochemical blood parameters indicate more intensive metabolic processes in the organism of cows with extended lactation period. In animals with prolonged lactation function, the adaptation index is negative and does not exceed ˗16.1 units, and in cows with prolonged lactation it reaches to ˗33.9 units. In such animals, as a consequence of the low reproductive function, the period of infertility increased significantly and, accordingly, a loss of calves and milk. It has been established that the higher productivity of the cows, the higher the cost of the obtained products and the additional feed costs do not exceed the cost of additional products, which ensures the economic efficiency of milk production.
Productive qualities of lactating cows during a long period of infertility
Keywords: індекс адаптації; index of adaptation; корови; cows; жива маса; live weight; лактація; lactation; безпліддя; infertility; удій; milk yield; масова частка жиру та білка; mass fraction of fat and protein; відтворна функція; reproductive function